14 Validation of transport systems to ensure quality of tissue delivered to eye banks. (16th November 2022) - Eagle, Mark; Rooney, Prof Paul
Abstract : Introduction: NHS Blood and Transplant Tissue and Eye Services (TES) retrieve eyes for corneal and scleral transplant purposes from hospitals, hospices, and funeral homes throughout the UK. The eyes are sent to TES eye banks either in Liverpool or Bristol. A major objective of TES is to ensure that the eyes arrive at their destinations in good condition and remain fit for purpose. With that in mind TES Research and Development have conducted a series of validation studies to ensure that eyes are packaged appropriately, and that the material is not damaged and maintains the required temperature during transport. Whole eyes are shipped on wet ice. Materials and Methods: Whole eyes – a corrugated plastic carton with an expanded polystyrene insert (Ocular Correx) had been used by Manchester and Bristol eye banks for at least 15 years before the eye banks joined TES. This original transport carton was compared with a re-useable Blood Porter 4 transport carton consisting of a single expanded polystyrene base and lid with a fabric outer packing. Porcine eyes were used secured in eye stands. T-class thermocouple probes were inserted through the lid s of 60 ml eye pots via pre-drilled holes, with the probe touching the outer surface of the eye, with probes routed under the boxes lid. For the original carton, three different weights of wet ice (1, 1.5, and 2 kg) were used inside the box, with the box placed in an incubator (Sanyo MCO-17AIC) at 37oC. Thermocouples were also placed in the wet ice and the incubator itself before they were connected to a calibrated datalogger (Comark N2014) which recorded the temperature every 5 minutes. For the Blood Porter carton a single 1.3 kg weight of ice was used Results: Whole eyes - tissue temperature was maintained between 2-8oC for 17.8 hours with 1 kg wet ice, 22.4 hours with 1.5 kg wet ice and 24+ hours with 2 kg wet ice. With the Blood Porter 4 box tissue temperature was maintained between 2-8oC for more than 25 hours with 1.3 kg wet ice. Discussion: Data reported in this study showed that both types of box are able to maintain tissue temperature between 2-8oC for at least 24 hours, provided the correct amount of wet ice is used. The data also showed that tissue temperature did not drop below 2oC, meaning there was no danger of the cornea potentially freezing.